HIV / AIDS in Africa : suffering women and the theology of the Book of Ruth - Van Dyk, Alta C. (Old Testament essays, 2002)
The story of HIV / AIDS in Africa and the Ruth narrative both describe the extraordinary suffering of women in the face of calamity. The plight of women in Africa has never been easy and the advent of HIV / AIDS did nothing to ease the suffering. The risk of becoming infected with HIV is two to four times higher for women than it is for men. Apart from their physical and biological vulnerability, women in Africa are particularly susceptible to HIV infection due to their lower social status, lack of control over their sexual lives, disempowerment and poverty. Exposure to diseases such as Tuberculosis and Malaria further exacerbates the problem. In the Book of Ruth we are also presented with two women who are also experiencing a major crisis. The legal status and social constraints of women such as Naomi and Ruth are analysed against four possible readings of the book. These four perspectives emphasise the responsibility for selfempowerment, the need to work positively towards solutions, the fact that it is sometimes necessary to change the structures of society, and the importance of sometimes cooperating with people in power.